GDAP1 Involvement in Mitochondrial Function and Oxidative Stress, Investigated in a Charcot-Marie-Tooth Model of hiPSCs-Derived Motor Neurons - Federica Miressi; Nesrine Benslimane; Frédéric Favreau; Marion Rassat; Laurence Richard; Sylvie Bourthoumieu; Cécile Laroche; Laurent Magy; Corinne Magdelaine; Franck Sturtz; Anne-Sophie Lia; Pierre-Antoine Faye (Biomedicines, 2021)
Mutations in the ganglioside-induced differentiation associated protein 1 (GDAP1) gene have been associated with demyelinating and axonal forms of Charcot-Marie-Tooth (CMT) disease, the most frequent hereditary peripheral neuropathy in humans. Previous studies reported the prevalent GDAP1 expression in neural tissues and cells, from animal models. Here, we described the first GDAP1 functional study on human induced-pluripotent stem cells (hiPSCs)-derived motor neurons, obtained from normal subjects and from a CMT2H patient, carrying the GDAP1 homozygous c.581C>G (p.Ser194*) mutation. At mRNA level, we observed that, in normal subjects, GDAP1 is mainly expressed in motor neurons, while it is drastically reduced in the patient’s cells containing a premature termination codon (PTC), probably degraded by the nonsense-mediated mRNA decay (NMD) system. Morphological and functional investigations revealed in the CMT patient’s motor neurons a decrease of cell viability associated to lipid dysfunction and oxidative stress development. Mitochondrion is a key organelle in oxidative stress generation, but it is also mainly involved in energetic metabolism. Thus, in the CMT patient’s motor neurons, mitochondrial cristae defects were observed, even if no deficit in ATP production emerged. This cellular model of hiPSCs-derived motor neurons underlines the role of mitochondrion and oxidative stress in CMT disease and paves the way for new treatment evaluation.